Представьте в виде многочлена выражение (2х-3у)² ​

yuliaatamanchuk yuliaatamanchuk    2   01.03.2021 09:55    1

Ответы
grebennickovasv grebennickovasv  31.03.2021 09:56

Объяснение:

(2x-3y)^2=4x^2-12xy+9y^2

ПОКАЗАТЬ ОТВЕТЫ
anya12345678900 anya12345678900  31.03.2021 09:56

4x^{2}-12xy+9y^{2}

Объяснение:

(a-b)^{2}=a^{2}-2ab+b^{2}; \quad (a \cdot b)^{n}=a^{n} \cdot b^{n};

(2x-3y)^{2}=(2x)^{2}-2 \cdot 2x \cdot 3y+(3y)^{2}=2^{2} \cdot x^{2}-12xy+3^{2} \cdot y^{2}=4x^{2}-12xy+9y^{2};

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра